Lambert-Eaton Myasthenic Syndrome: A Review of Rare Neuromuscular Disease Related to Paraneoplastic and Autoimmune - Fardhani, Ichlasul Mahdi; Graciella, Cindy; Rayyan, Muhammad Isra Rafidin (AKSONA, 2025)
Highlight: LEMS is a rare neurological disease with fluctuating symptoms Delays and misdiagnosis of LEMS disease often occur The two main pathophysiologies of LEMS are autoimmune and paraneoplastic.   ABSTRACT A rare condition known as Lambert-Eaton myasthenic syndrome (LEMS) affects the neuromuscular junctions, which are the connections between muscles and nerves. Tumor-associated or autoimmune causes trigger this condition. This mechanism depends on the presence of antibodies that directly attach to voltage-gated calcium channels located on the presynaptic nerve terminals. LEMS disease is divided into non-paraneoplastic or non-tumor LEMS (NT-LEMS) and paraneoplastic LEMS (P-LEMS). NT-LEMS is believed to be caused by an autoimmune process. On the other hand, P-LEMS has an underlying tumor, and LEMS symptoms are paraneoplastic manifestations of the tumor. Clinical signs of LEMS include proximal muscle weakness, autonomic dysfunction, and decreased deep tendon reflexes. The predominant sign of LEMS is weakness of the lower extremities. The defining characteristic of LEMS is a weakness that spreads from caudal to cranial, causing oculobulbar manifestations, and from proximal to distal, potentially involving the feet and hands. The diagnosis of LEMS depends on clinical, electromyographic, and serological findings of anti-VGCC antibodies. Therefore, comprehensive oncologic screening and monitoring should promptly follow a diagnosis of LEMS. The standard approach to treating LEMS symptoms is administering drugs that improve neurotransmission, such as potassium channel blockers and amifampridine. In refractory cases, immunosuppressants or immunomodulator agents, such as a combination of prednisone and azathioprine, are used. If a tumor is detected, oncological therapy should be a priority.